Settlement of TNI Servant LGBT Cases in The Military Justice System - Prastiti Siswayani; Nurini Aprilianda; Faizin Sulistyo (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
The LGBT (Lesbian, Gay, Bisexual, and Transgender) community represents a sexual orientation and behavior that diverges from religious doctrine and societal norms in Indonesia. Recent revelations have shown instances of LGBT behavior among TNI soldiers, prompting discussions on how the Military Justice system handles such cases. This study delves into the philosophical underpinnings of the Panel of Judges' considerations regarding evidence of criminal acts related to LGBT behavior, particularly focusing on Article 103 of the Indonesian Criminal Code and Military Criminal Law. Utilizing a normative research approach with a comparative perspective on judicial decisions from two military courts, the research aims to provide insights into the resolution of LGBT-related cases within the military context. Ultimately, it concludes that LGBT behavior within Military Courts constitutes immoral conduct and may result in severe sanctions under the provisions of Articles 281 and 103 of the Criminal Code